2016
DOI: 10.1186/s12866-015-0622-2
|View full text |Cite
|
Sign up to set email alerts
|

Colonization potential to reconstitute a microbe community in patients detected early after fecal microbe transplant for recurrent C. difficile

Abstract: BackgroundFecal microbiota transplants (FMT) are an effective treatment for patients with gut microbe dysbiosis suffering from recurrent C. difficile infections. To further understand how FMT reconstitutes the patient’s gut commensal microbiota, we have analyzed the colonization potential of the donor, recipient and recipient post transplant fecal samples using transplantation in gnotobiotic mice.ResultsA total of nine samples from three human donors, recipient’s pre and post FMT were transplanted into gnotobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…This study provides additional evidence linking the human intestinal microbiota with the pathogenesis of arthritis. We did not demonstrate differences in the extent of arthritis between mice colonized with patient versus control microbiota, findings that could be attributed to the failure of human-mouse FMT to recapitulate the precise microbial contents of the human donors, as observed herein ( Figure 3 ) and previously [ 11 , 12 ]. Our prior work demonstrated that a subset of children with ERA demonstrated a high intestinal abundance of A. muciniphila [ 1 ].…”
Section: Discussionsupporting
confidence: 72%
“…This study provides additional evidence linking the human intestinal microbiota with the pathogenesis of arthritis. We did not demonstrate differences in the extent of arthritis between mice colonized with patient versus control microbiota, findings that could be attributed to the failure of human-mouse FMT to recapitulate the precise microbial contents of the human donors, as observed herein ( Figure 3 ) and previously [ 11 , 12 ]. Our prior work demonstrated that a subset of children with ERA demonstrated a high intestinal abundance of A. muciniphila [ 1 ].…”
Section: Discussionsupporting
confidence: 72%
“…Mice were housed by human sample chemotherapy status and diet [ Table 1 ] (4 mice/ cage- a total 48 mice in 12 cages). Fecal suspension (200 μl) was transplanted into mice using oral-gavage and enema routes [ 35 ]. Co-housing of four GF mice with one colonized mouse led to successful colonization of all four GF mice.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were individually housed in separate isolators in the UAB Gnotobiotic Facility, and sterile (autoclaved) mouse chow (Teklad #2019S) was supplied ad libitum. Previously, we determined that two weeks post-transplant was sufficient to allow re-constitution of an intact microbiome [22].…”
Section: Faecal Transplantation Of Gnotobiotic Micementioning
confidence: 99%
“…Faecal samples from individual mice were processed for DNA as previously described [22]. The DNA from a total of 30 faecal samples (5 human faeces, 5 dam faeces and 20 F1 progeny faeces) was prepared, processed and sequenced using the Illumina NextSeq platform, with 150 base paired-end reads with an average of 17 million reads per sample (electronic supplementary material, table S1).…”
Section: Metagenomic Sequencing Of Murine Faecal Samplesmentioning
confidence: 99%